Anti-Apoptotic Effect of Flavokawain A on Ochratoxin-A-Induced Endothelial Cell Injury by Attenuation of Oxidative Stress via PI3K/AKT-Mediated Nrf2 Signaling Cascade - Peramaiyan Rajendran (MDPI AG, 2021)
This study investigates the endothelial protective activity of flavokawain A (FKA) against oxidative stress induced by ochratoxin A (OTA), which acts as a mycotoxin, and its primary mechanisms in in vitro models. Reactive oxygen species, in general, regulate oxidative stress that significantly contributes to the pathophysiology of endothelial dysfunctions. OTA exerts toxicity through inflammation and the accumulation of ROS. This research is aimed at exploring the defensive function of FKA against the endothelial injury triggered by OTA through the Nrf2 pathway regulated by PI3K/AKT. OTA exposure significantly increased the nuclear translocation of NFκB, whereas we found a reduction in inflammation via NFκB inhibition with FKA treatment. FKA increased the PI3K and AKT phosphorylation, which may lead to the stimulation of antioxidative and antiapoptotic signaling in HUVECs. It also upregulated the phosphorylation of Nrf2 and a concomitant expression of antioxidant genes, such as HO-1, NQO-1, and γGCLC, depending on the dose under the oxidative stress triggered by OTA. Knockdown of Nrf2 through small interfering RNA (siRNA) impedes the protective role of FKA against the endothelial toxicity induced by OTA. In addition, FKA enhanced Bcl2 activation while suppressing apoptosis marker proteins. Therefore, FKA is regarded as a potential agent against endothelial oxidative stress caused by the deterioration of the endothelium. The research findings showed that FKA plays a key role in activating the p-PI3K/p-AKT and Nrf2 signaling pathways, while suppressing caspase-dependent apoptosis.